Identifikasi Kesesuaian Lokasi Tempat Evakuasi Sementara Menggunakan Intersect-Overlay di Kabupaten Banggai Kepulauan - Fathurrahman Burhanuddin; Soemitro Emin Praja (Universitas Muslim Indonesia, 2023)
The Regional Spatial Plan (RTRW), a spatial planning instrument in the district area, needs to pay attention to and consider the form of mitigation in disaster-prone areas. Spatial planning disaster mitigation is planned as an evacuation route and an evacuation site, specifically an evacuation site is referred to as a temporary evacuation site (TES). The research location is in the Banggai Islands Regency by reviewing the suitability of TES in the Regency spatial planning (RTRW). The purpose of the research is to determine the suitability of the TES location plan that has been planned in the spatial planning (RTRW) with several assessment parameters. This study uses an intersect-overlay analysis with several assessment parameters, namely disaster-prone areas, availability of accessibility, spatial pattern plans, and activity function of the TES location. The results of this study are more of a comparative study of the suitability of the TES location plan that has been planned in the spatial planning (RTRW) with the assessment parameters in several previous studies so the TES location needs to be reviewed regarding suitability in determining the TES location in the Banggai Islands Regency spatial planning document.